Frequency-Dependent Relationship Between Resting-State fMRI and Glucose Metabolism in the Elderly - Jiao, Fangyang; Gao, Zhongzhan; Shi, Kuangyu; Jia, Xize; Wu, Ping; Jiang, Chengfeng; Ge, Jingjie; Su, Hui; Guan, Yihui; Shi, Shenxun; Zang, Yu-Feng; Zuo, Chuantao (Frontiers in Neurology, 2019)
Both glucose metabolism and blood-oxygenation-level dependent fMRI (BOLD-fMRI) signal reflect hemodynamic features. The objective of this study was to investigate their relationship in the resting-state in healthy participants (n = 18). For fMRI signal, regional homogeneity (ReHo), amplitude of low frequency fluctuations (ALFF), fractional ALFF (fALFF), and degree of centrality (DC) maps were generated in multiple frequency bands. Glucose uptake was acquired with 18F-fluorodeoxyglucose positron emission tomography (FDG-PET). Linear correlation of each pair of the FDG-PET and BOLD-fMRI metrics was explored across voxels in the whole brain and voxel-wise across subjects. Additionally, the partial volume effect on the FDG-PET and the head motion effect on fMRI may affect these results and were also taken into account in the data processing. Finally, we identified a mild but significant correlation between the FDG-PET and BOLD-fMRI metrics across voxel within the whole brain. The across-subject correlation analysis showed that only a small portion of voxels showed significant correlation between FDG-PET and BOLD-fMRI metrics, indicating that FDG-PET and BOLD-fMRI metrics are not correlative and different. Specifically, FDG-PET measures the mean glucose metabolism over a period of time, while BOLD fMRI measures the dynamic characteristics. The combination of FDG-PET and BOLD-fMRI provides complementary information to reveal the underlying mechanisms of the brain activity and may enable more complete interpretation of clinical PET-fMRI studies.